Karakteristik Sifat Sensori dan Daya Terima Cookies Substitusi Tepung Ubi Ungu Dan Tepung Sukun - Indriyani, Merry; Hartati, Yuli; Sartono, Sartono; Siregar, Afriyana (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2022)
Background : Cookies are a type of pastries made from a soft and crunchy dough, high in fat content, and when broken, the cross-sectional texture is not too dense. Cookies with the substitution of purple yam flour and breadfruit flour which are rich in fiber are also very suitable to be consumed as a snack for diabetes mellitus patients. Purpose: The purpose of the study was to determine the acceptance test of purple sweet potato flour and breadfruit flour cookies as a snack in patients with type II diabetes mellitus. Methods: This study used an experimental study with a non-factorial Completely Randomized Design (CRD). Using Organoleptic Test with a panel of 50 people. Determination of nutritional value and fiber using proximate analysis and fiber analysis. Acceptance test using Friedman test. Results: The selected purple sweet potato and breadfruit flour cookie formulations were F1 (30 grams of purple sweet potato flour and 10 grams of breadfruit flour) with an energy content of 497.35 Kcal, 8.5% protein, 29.79% fat, 48 carbohydrates, 81%, 10.79% moisture content, 2.11% ash content, and 13.17% fiber in 100 g cookies. Based on the Friedman test, there is a relationship between the acceptance of purple sweet potato flour and breadfruit flour cookies in terms of aroma (p = 0.031) and taste (p = 0.006). Meanwhile, in terms of color and texture, there was no relationship between the acceptance of purple sweet potato flour and breadfruit flour cookies in terms of color (p = 0.836) and texture (p = 0.977). Conclusion: purple sweet potato flour and breadfruit flour cookies can be used as an alternative snack for people with diabetes mellitus.